Perspective on the Use of Ultrasonic Monitoring for In Situ Diagnostics of Zeolite and MOF Crystallization - Ermer, Matthias; Reber, Rebecca; Baser, Hasan-Hüseyin; Fischer, Marcus; Schwieger, Wilhelm; Hartmann, Martin (Crystal Growth and Design, 2023)
The investigation and understanding of the underlying mechanisms for the crystallization of molecular sieve materials, such as metal-organic frameworks (MOFs) and zeolites, have received increasing interest in recent years. This is mainly because improvements of the corresponding equipment were made that are essential for in situ diagnostics. In contrast to classical techniques, such as X-ray diffraction and neutron scattering, nuclear magnetic resonance, or infrared and Raman spectroscopy, ultrasonic monitoring has not received proper attention. Thereby, especially for zeolites, important insights have been gained with this technique already. However, for MOFs, the number of publications dealing with in situ US monitoring is still limited. Therefore, this perspective gives an overview of the topic of in situ monitoring of crystallization of zeolites and MOFs and highlights the work that has been done so far by ultrasonic monitoring. Furthermore, we state benefits and current challenges for further establishing ultrasonic monitoring as a tool for the investigation of crystallization processes.
CRIS-Team Scopus Importer:2023-07-21